Simulação da evolução da Camada Limite Planetária Amazônica em eventos de convecção profunda utilizando o modelo WRF - Oliveira, Marcio Augusto Gonçalves (2023)
The convection in the Amazon basin and its impacts on the Planetary Boundary Layer (PBL) are extremely complex, the present study made two simulations using the Weather Research and Forecasting (WRF) model with different microphysical schemes, the simulation I used the Thompson scheme and the II used the National Severe Storms Laboratory (NSSL) scheme, in order to reproduce the same BPL environment previously observed in Oliveira et al. (2020), which observed a deep convection event that occurred on October 31 2015, at approximately 17:15 local time (LT), on the Amazon Tall Tower Observatory (ATTO) site located in the central part of the Amazonas state. Convection was better represented in the II simulation, the I simulation produced less convective cells, but both produced a good amount of deep cells. The meteorological variables in both simulations behaved in a relatively similar way to those observed, but the model overestimated the states prior to the arrival of the system, the drops in temperature and increase in wind speed were well represented in both, as well as the formation of a pool cold, a mechanism that helped in its propagation. With this, the present study seeks to contribute to the understanding of the interaction between deep convection and the Amazonian surface, in addition to demonstrating the difficulties of carrying out studies involving numerical simulation in the Amazon region and serving as a comparison for future studies.